Comprehensive Physiology 1997
DOI: 10.1002/cphy.cp130108
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate Renal System

Abstract: The sections in this article are: External and Internal Gross Morphology of Vertebrate Kidneys Fishes Amphibians Reptiles Birds Mammals Glomerular Ultrafiltration Glomerular Filtration Rate: Stability and Variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 268 publications
2
31
0
1
Order By: Relevance
“…Similarly, excess water may be excreted at the expense of salt [17,70], or it may perhaps be retained in the body to prevent acute salt loss [10]. During dehydration or salt loading, the inulin U/P ratio or creatinine U/P ratio increases in reptiles and birds, indicating that renal tubules effectively absorb water [11,70]. In contrast, significant tubular water absorption continues during water loading in desert quail; only 79% of loaded water is excreted, despite the increase in single nephron GFR and the number of filtering nephrons [10].…”
Section: Renal Responses To Osmotic Challengesmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, excess water may be excreted at the expense of salt [17,70], or it may perhaps be retained in the body to prevent acute salt loss [10]. During dehydration or salt loading, the inulin U/P ratio or creatinine U/P ratio increases in reptiles and birds, indicating that renal tubules effectively absorb water [11,70]. In contrast, significant tubular water absorption continues during water loading in desert quail; only 79% of loaded water is excreted, despite the increase in single nephron GFR and the number of filtering nephrons [10].…”
Section: Renal Responses To Osmotic Challengesmentioning
confidence: 98%
“…A larger urine flow may be required for birds to excrete uric acid and other metabolic products. In nonmammalian vertebrates, GFR is controlled intermittently [11,16]. In this context, caution is needed in interpreting the percentage of filtered water excreted/reabsorbed.…”
Section: Renal Responses To Osmotic Challengesmentioning
confidence: 98%
See 1 more Smart Citation
“…Embryologically, the head kidney and trunk kidney are derived from the pronephros and mesonephros, respectively (Romer and Parsons 1977). The head kidney is the anterior portion of the kidney and probably has no renal function (Braun and Dantzler 1997) as it consists primarily of lymphoid tissue, whereas the trunk kidney is composed of many nephrons and interstitial lymphoid tissue (Hickman and Trump 1969). Our observations have specifically dealt with the morphology and function of the trunk kidney.…”
Section: Kidney Morphologymentioning
confidence: 99%
“…Studies on the nephrons of trout, killifish, and other species have demonstrated distinct functional differences between the tubule segments (Braun and Dantzler 1997) and specific differential localization of transporters (Miyazaki et al 2002). Nishimura et al (1983) have shown that, in the distal tubule, chloride efflux (lumen to bath) is significantly higher than chloride influx (bath to lumen), suggesting the net Cl -reabsorption from the lumen to the bath and with a lumen-positive transepithelial voltage.…”
Section: Introductionmentioning
confidence: 98%